Chronic cholecystitis at patients with the various trophological status: mechanisms and feature of clinical course - Ye. V. Anisimova; I. V. Kozlova; S. V. Volkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To analyze clinical, biochemical features of various forms of pathology of a gallbladder in view of features of food behavior and factors of its regulation at patients with the various trophological status.Material and methods. Overall 167 patients with gallbladder diseases and various trophological status were included in original study. Food behavior analysis was carried out, clinical features, anthopometry were determined, bile lipid spectrum, serum content of leptin and insulin were studied by enzyme-linked immunoassay.Results. Investigation of gallbladder diseases has objectively demonstrated, that trophological status affects development and course of chronic cholecystitis, but is not the only determining factor.Conclusions. Development and course of gallbladder diseases are defined by trophological status based on disorders of food behavior, change of production of leptin, insulin.